Assessing the pattern of utilization of wild plants for medicinal purpose : the case of bidayuh Tebia of Kampung Kiding, Padawan, Sarawak - Margarita, Naming (Universiti Malaysia Sarawak (UNIMAS), 2015)
Globally, medicinal plants have contributed to the discovery of important compounds with new use and especially for drugs. This gives rise to the world‘s interests in exploring and documenting the traditional knowledge of how local and indigenous communities around the world use plant resources. There is a great concern that the knowledge of the communities are diminishing due to the passing of the older generation and the change in land-use and lifestyle of the younger generation. Hence, this study aims to document the knowledge of the community and the distribution pattern of the medicinal plants among the Bidayuh of Kampung Kiding, Sarawak. A total of 35 species of plants belonging to 25 family were documented on its uses for medicinal purposes. Of these, 72% (27 species) of the plant species were medicinal plants for external use, 16% (6 species) for internal use, 8% (3 species) for healing of disease caused by ‗black magic‘ or spirits and 3% (1 species) was for preventing hair fall and itchy scalp. Among the three vegetation sites, the agroforestry site recorded the highest number of species (28 species) followed by the old rubber farm (14 species) and secondary forest (13 species). The high number of species in the agroforestry site is due to the accessibility to the area by the community. Hence, more useful plant species are planted. Though, the Shannon-Weiner index showed that the old rubber farm has the highest diversity index, the analysis of variance for diversity indices in the three vegetation types indicates that there is no significant difference (F= 1.4228; P-value of 0.2585). The plant Selaginella sp. recorded the highest number of individual at all three sites. The community of Kampung Kiding value medicinal plants based on the people‘s affordability and there is no fix payment for the medicinal plants. For conservation purposes, the community is willing to pay RM30 as labour to maintain medicinal plant in an area.